Wire outlet end of anti-winding pet tractor and anti-winding pet tractor - TANG WENWEI; DAI QINGFENG (2021)
The utility model provides an anti-winding leading-out terminal of a pet tractor, which comprises a transversely arranged crescent-shaped leading-out port for a rope to go in and out and one or two broken line arc ports arranged on the upper edge of the leading-out port. The utility model further provides an anti-winding pet tractor which comprises a shell, a wire coil arranged in the shell and a rope wound on the wire coil, and the wire outlet end for the rope to go in and out is arranged on the shell. The wire outlet end of the pet leash is originally provided with the two fold line arc openings, a pet rope can enter the pet leash more smoothly when the pet leash is taken back, the phenomena of winding and knotting are not prone to being caused, operation is easy and convenient, and the use experience feeling is better. 本实用新型提供了一种防缠绕宠物牵引器的出线端，所述出线端包括横向设置的月牙状的供绳进出的出线口及设置在所述出线口上沿的折线圆弧口，所述折线圆弧口为1个或2个。本实用新型还提供了一种防缠绕宠物牵引器，它包括外壳及设置在外壳内的线盘、线盘上饶设的绳，所述外壳上设置有如上所述的供绳进出的出线端。本实用新型提供的宠物牵引器的出线端独创性的设置了两个折线圆弧口，用于宠物绳在收回时更顺畅的